Thermal stability of extracellular hemoglobin of Rhinodrilus alatus (HbRa): DLS and SAXS studies - Carvalho, Jose Wilson P.; Carvalho, Francisco A. O.; Santiago, Patricia S. [UNESP]; Tabak, Marcel (Springer, 2016)
Oxy-HbRa thermal stability was evaluated by dynamic light scattering (DLS) and small-angle X-ray scattering (SAXS) at pH 5.0, 7.0, 8.0, and 9.0. DLS results show that oxy-HbRa, at pH 7.0 and 5.0, remains stable up to 56 degrees C, undergoing denaturation/aggregation in acidic media above 60 degrees C, followed by partial sedimentation of aggregates. At alkaline pH values 8.0 and 9.0, oxy-HbRa oligomeric dissociation is observed above 30 degrees C, before denaturation. SAXS data show that oxy-HbRa, at 20 degrees C, is in its native form, displaying radius of gyration (R-g) and particle maximum dimension (D-max) of 108 +/- 1 and 300 +/- 10 angstrom, respectively. Oxy-HbRa, at pH 7.0, undergoes denaturation/aggregation at 60 degrees C. At pH 5.0-6.0, HbRa thermal denaturation/aggregation start earlier, at 50 degrees C, accompanied by an increase of R-g and D-max values. However, an overlap of oligomeric dissociation and denaturation in the system is observed upon temperature increase, with an increase in R-g and D-max. Analysis of experimental p(r) curves as a linear combination of theoretical curves obtained for HbGp fragments from the crystal structure shows an increasing contribution of dodecamer (abcd)(3) and tetramer (abcd) in solution, as a function of pH values (8.0 and 9.0) and temperature. Finally, our data show, for the first time, that oxy-HbRa, in neutral and acidic media, does not undergo oligomeric dissociation before denaturation, while in alkaline media the oligomeric dissociation process is an important step in the thermal denaturation.
Keywords: Erythrocruorins; Thermal stability; Denaturation/aggregation; Oligomeric dissociation; pH